Uncovering the antifungal potential of Cannabidiol and Cannabidivarin - Dinh, Hue; Fernandes, Kenya E.; Erpf, Paige E.; Clay, Evie J. M.; Tay, Aidan P.; Nagy, Stephanie S.; Schaefer, Sebastian; Maharjan, Ram; Lenardon, Megan D.; Multari, Dylan H.; Haynes, Paul A.; Paulsen, Ian T.; et al. (PLOS Neglected Tropical Diseases, 2025)
Fungal infections pose a major threat to human health with increasing incidence of antifungal resistance globally. Despite the need for novel antifungal drugs, few are currently in clinical development. Here we evaluate the antifungal activity of five phytocannabinoids against several clinically relevant fungal pathogens, with a focus on the priority pathogen Cryptococcus neoformans. Our results demonstrate that Cannabidiol (CBD), and particularly Cannabidivarin (CBDV), have broad activity against C. neoformans and other fungal pathogens, including dermatophytes that cause common tinea. We found that both CBD and CBDV acted in a fungicidal manner and prevented biofilm formation in C. neoformans. Phytocannabinoid treatment impeded factors important for virulence and antifungal resistance, including reduced capsule size and disruption of mature biofilms. Proteomics analysis revealed that the antifungal activity of CBD and CBDV was linked to destabilisation of the membrane, alterations in ergosterol biosynthesis, disruption of metabolic pathways, as well as selective involvement of mitochondrial-associated proteins. We next tested the ability of CBD to topically clear a C. neoformans fungal infection in vivo using the Galleria mellonella burn wound model, and we observed greatly improved survival in the CBD treated larvae. This study illustrates the potential of phytocannabinoids as antifungal treatments and opens up new routes towards development of novel antifungal drugs.